Degradação forçada dos fármacos nitazoxanida e sofosbuvir e degradação térmica de dispersões sólidas amorfas contendo ritonavir - Alvarenga Junior, Benedito Roberto de (2022)
The first chapter of this work aimed to use design of experiments in the forced degradation of sofosbuvir (SOF) and nitazoxanide (NTZ). The variables pH, temperature and interaction between temperature and H2O2 contributed to degrade SOF in the experiments with no UV light. SOF presented lower stability at pH 1 in the experiments with UV light. The variables pH, temperature, H2O2, and the interaction between pH and temperature contributed to degrade NTZ in the experiments with no UV light. In the experiments with UV light it was not noticed influence of pH and temperature on NTZ degradation, but a synergism effect of these variables was observed. It was elucidated 10 degradation products of SOF (P1-P10) and 5 (D1-D5) for NTZ by LC-MS/MS. The second chapter was destinated to evaluate the thermal stability of RTV in amorphous solid dispersions. The samples were thermally degraded by thermogravimetry, conventional oven, and hot-melt extrusion. Thermal stability of RTV was related to substituent groups of polymers, which protic ones (hydroxypropyl methylcellulose acetate succinate (HPMCAS), and hydroxypropyl methylcellulose (HPMC)) catalyzed degradation reactions of RTV when compared with aprotic polymers (poly(vinylpyrrolidone) (PVP), copovidone (PVP/VA)). Few evidences showed that thermal stability of RTV is related to molecular mobility or molecular interactions in RTV formulations. The RTV degradation products (R1-R7) were generated from hydrolysis reactions, except R4 which raised of RTV dehydration. Both works were fundamental to understand the process of degradation and the drugs stabilities in different chemical environments.